Improving call center performance - Ranta, Roope (My University, 2018)
The study problem was to find a way to improve call center performance. The method of study was to combine existing articles and studies to form a clear path for call centers to use to improve their performance. The most important source of information were articles and case studies produced on the subject. The goal of this research was to demonstrate different ways to measure and improve the performance of a call center. The research focuses on three different point of views: Call center, call center agent and call center manager. The most important result of this study were the tools for the call centers to use to improve their performance.
Keywords: Call center; performance; efficacy; operational efficiency; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|